Konsep Israf dan Keseimbangan Konsumsi dalam QS. Al-A’raf Ayat 31: Tinjauan Tafsir dan Ekonomi Islam - Luthfiah Al Asbin Ulyani; Nurhayati; Yenni Samri Juliati Nasution (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the concept of israf (extravagance) and consumption balance as stated in Surah Al-A’raf verse 31 through a comparative interpretation of classical and contemporary exegeses, and to integrate these insights with Islamic economic principles. This research employs a library-based qualitative method by examining Qur’anic texts, tafsir literature, and recent academic studies related to Islamic consumption ethics. The findings indicate that the verse highlights three essential principles: the command to adorn oneself properly when attending the mosque, the permissibility of eating and drinking within reasonable limits, and the firm prohibition of extravagance due to its harmful effects on individuals and society. The study also shows that the principle of balanced consumption (moderation) forms a foundational value in Islamic economics, supporting the objectives of Shariah in preserving life, wealth, and intellect. Furthermore, the study underscores the relevance of Qur’anic guidance on moderation in addressing modern challenges such as consumerism, wastefulness, and environmental degradation. It concludes that the Qur’anic teachings on consumption provide a comprehensive ethical and economic framework for achieving well-being and sustainability.